Projeto, construção e levantamento de desempenho de um concentrador solar cilíndro parabólico com mecanismo automático de rastreamento solar - Souza Filho, José Ribeiro de (2008)
An cylinder-parabolic solar concentrator is presented to produce steam for different applications. This prototype was built in glass fiber with dimensions that follow a study of optimization of parameters inherent in the optical reflection of sunlight by the surface of reflection and absorption of the same by tubing that leads the fluid of work. The surface of the concentrator of 2.24 m² has been covered by layers of mirror with 1.0 m of lenght and 2.0 cm wide. The absorb tubing consists of a copper tube diameter equal to 28 mm. The concentrator is moving to follow the apparent motion of the sun. It will be presented the processes of manufacturing and assembly of the concentrator proposed, which has as main characteristics the facilities construction and assembly, in addition to reduced cost. Will be presented data from tests performed to produce steam setting up some parameters that diagnose the efficiency of the concentrator. It will be demonstrated the viabilities thermal, economic and of materials of the proposed system.The maximum temperature achieved in the vacuum tube absorber was 232.1°C and average temperature for 1 hour interval was 171.5°C, obtained in a test with automation. The maximum temperature achieved in the output of water was 197.7°C for a temperature of 200.0°C in the absorber tube. The best average result of the water exit temperature to interval of 1 hour was 170.2°C for a temperature of 171.2°C, in the absorber tube, obtained in test with automation. Water exit mean temperatures were always above of the water steaming temperature. The concentrator present a useful efficiency of 38% and a production cost of approximately R$ 450,00 ( $ 160.34)